Qual o lugar das mulheres no mundo? O peso dos estereótipos de gênero sobre as mulheres migrantes e refugiadas - Costa, Marli Marlene Moraes da (2018)
Throughout life, women and men are confronted with expectations about their behavior and their “place” in society. These “gender expectations” usually start from preconceptions that limit women’s lives, either by emphasizing their role as wife and mother, or what kind of attitude they should have in both domestic and work environment. These stereotypes, based on gender, reflect the sexual division of labor, the different forms of violence suffered by women, the determination of which spaces they can occupy, the pressure on the type of life and behaviors (marriage, maternity, clothing,…), in the objectification of women’s bodies and in the difficulty of overcoming the structures of power that order society. These situations are common to all women, but for women in a situation of migration they are an aggravating factor in that they are more unprotected to claim and have access to rights. The present paper aims to analyze the gender stereotypes of migrant and refugee women, based on the question of the place of women in the world. In this way, it will first deal with gender stereotypes and their influence on women’s lives in general, and then approach the lives of women in a world of men, in view of the androcentric vision of the world constantly reinforced in different spaces. Finally, it will analyze the gender stereotypes of migrant and refugee women. It is a bibliographical review, based on the deductive method, in order to corroborate the hypothesis that women and men are placed in front of gender stereotypes, but the negative burden on women is much higher due to the conception of male and female socially reproduced, which will also be reflected in the migratory context.